Facility-based capacity assessment of emergency care services in public hospitals in Zambia - Chavula, Chancy (Division of Emergency Medicine, 2017)
In sub-Saharan Africa, the shift in disease burden from infections to non-communicable disease and injury highlights the need for effective and efficient emergency care. Despite this, emergency care is a neglected sector of the health system in most low and middle-income countries. Funding and resource allocations are often small and have little impact on the development of emergency care systems, and provision of emergency care is therefore frequently left to under-trained and/or under-prepared nurses or clinical officers. In order to develop effective emergency care systems, one must first identify strengths and challenges in existing systems. The aim of this study was to determine facility-based emergency care capacity in public hospitals in Zambia. This descriptive cross-sectional study comprised of a total of 23 facilities: seven districts, 12 general and four central hospitals. Data were collected using a standardised Emergency Care Assessment Tool (ECAT); developed in 2013 by AFEM to ascertain facilities' strengths and weaknesses in the delivery of the emergency care services for five sentinel conditions and maternal health. The ECAT was administered through one-on-one interviews with designated personnel working in emergency receiving areas. The assessment tool consists of six main themes relating to the ability to provide care for patients suffering from respiratory failure, shock, altered mental status, severe pain, trauma and maternal health. The majority of facilities were able to perform almost all the procedures across all themes. However, some procedures, which were highly technical and required personnel with specialist training or specialised equipment, were not performed at all facilities. The level of the facility also dictated whether a procedure could be performed where higher-level health facilities like central hospitals were able to perform more procedures than lower-level facilities due to higher numbers of trained personnel, more equipment and supplies, and better infrastructure. Maternal health was covered in almost all (>90%) hospitals. Across all themes, the most frequent reasons for not performing procedures were lack of supplies (n=137) followed by no training (n=136), no infrastructure (n=35) and no human resources (n=34). At the central level, the most frequent reason for not performing procedures was no supplies (n=16), whereas at district and general levels the most frequent reason was no training. Overall, most facilities were able to offer basic emergency care services. However, there is limited capacity of training and supplies across all facilities, as well as a lack of infrastructure and policies for emergency care in lower-level facilities. Zambian hospitals can provide basic emergency care, but there is need to enhance training and improve on provision of supplies to enable facilities to provide emergency care. Focus must also be on development of policies relating to emergency care to guide and standardise procedures. Capacity building should be more focused at district and general hospitals to improve emergency care across all levels of health facilities, as it will reduce the burden at central level and improve patient outcomes since these are first-line access points for patients.